Implications of Capital Availability and Accessibility on Entrepreneurial Propensity of Graduate Students in Ghana - De-Graft Owusu-Manu; Sakibu Seidu; R. Nyadu-Addo; David John Edwards; Kwaku Ankamang Frimpong (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Purpose: Many graduates want to become entrepreneurs and set up their own companies to provide employment and future security for them. However, most graduates face limited capital accessibility that could facilitate their entrepreneurial desires. This study was conducted to assess the implications of capital availability and accessibility on graduates’ propensity towards their entrepreneurship development. Methodology: A quantitative strategy and deductive reasoning were adopted to analyze primary data obtained from structured and close-ended questionnaires. The population constituted graduates in Ghana and since the number is infinite and difficult to determine, Cochran’s formula was used to obtain a sufficient sample size of 384.384 questionnaires were therefore distributed using a convenience sampling technique. 342 questionnaires (representing over 89% response rate) were retrieved for analyses. Correlation, Mean score and relative importance index were employed in analyzing the data. Findings: Findings reveal that the availability of funding is a catalyst for graduates to venture into entrepreneurship as capital investment made graduates focused and motivated and therefore, able to succeed in business. More than 70% of graduates agree that capital availability was their deciding factor in starting their own businesses. The study established that capital accessibility is needed to help graduates: acquire skills; pursue entrepreneurship as a career option; and bring about wider innovation and renewed growth within Ghana’s economy. Practical Implications The implications are in the areas of policy and reformations that could create a positive graduate proclivity towards entrepreneurship. Originality: This paper constitutes a modern appraisal of the effect of capital availability and accessibility on graduate’s propensity towards entrepreneurship.